Diabetic Bulla : A Rare Distinct Diabetic Marker - Fernandes Caroi Z; Bhat Ramesh (Wolters Kluwer Medknow Publications, 2002)
The appearance of spontaneous blisters that are usually confined to the hands and feet is a rare but specific event in diabetes mellitus. We present a case of diabetic bulla in a 60 year old male diabetic patient for its rarity.